2017
DOI: 10.1038/srep43393
|View full text |Cite
|
Sign up to set email alerts
|

MiR-139-5p as a novel serum biomarker for recurrence and metastasis in colorectal cancer

Abstract: Approximately 30–50% of colorectal cancer (CRC) patients who undergo curative resection subsequently experience tumor recurrence or metastasis. Although microRNAs (miRNAs) are a class of small noncoding RNAs frequently deregulated in various human malignancies, it remains unknown if these can help predict recurrence and metastasis in CRC patients. MiRNAs were initially screened using miRNA-microarray and miRNA-seq datasets with or without recurrence. Candidate miRNAs were then tested in two independent cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 49 publications
0
40
1
1
Order By: Relevance
“…Although we do not have explanation for this discrepancy, one should mention that in Ozata's study, the concentrations of miRNA inhibitors used are 20 times higher than those we have tested in the present work . MiR‐139‐5p, which resides within intron 2 of PDE2A gene, has been reported to be downregulated and to display anti‐oncogenic and anti‐metastatic activities in human cancers . We found that miR‐139‐5p is upregulated in ACC patient samples as well as in NCI H295R cells in which it acts as pro‐invasive miRNA.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although we do not have explanation for this discrepancy, one should mention that in Ozata's study, the concentrations of miRNA inhibitors used are 20 times higher than those we have tested in the present work . MiR‐139‐5p, which resides within intron 2 of PDE2A gene, has been reported to be downregulated and to display anti‐oncogenic and anti‐metastatic activities in human cancers . We found that miR‐139‐5p is upregulated in ACC patient samples as well as in NCI H295R cells in which it acts as pro‐invasive miRNA.…”
Section: Discussioncontrasting
confidence: 56%
“…15 MiR-139-5p, which resides within intron 2 of PDE2A gene, has been reported to be downregulated and to display anti-oncogenic and antimetastatic activities in human cancers. 40 We found that miR-139-5p is upregulated in ACC patient samples as well as in NCI H295R cells in which it acts as pro-invasive miRNA. Our result showing for the first time that miR-139-5p is a powerful prognostic factor for survival of ACC patients supports its role in ACC aggressiveness.…”
Section: Discussionmentioning
confidence: 72%
“…Miyoshi et al, 6 who reported miR-139-5p upregulation in the serum samples of recurrence-positive CRC patients, added 25 fmol of cel-miR-39 to each sample for data normalization. Cel-miR-39, which is derived from Caenorhabditis elegans, is a synthetic microRNA that is used for microRNA normalization in the recent studies, and in this section we summarize some of the research that normalized values using cel-miR-39.…”
mentioning
confidence: 99%
“…Cel-miR-39, which is derived from Caenorhabditis elegans, is a synthetic microRNA that is used for microRNA normalization in the recent studies, and in this section we summarize some of the research that normalized values using cel-miR-39. Miyoshi et al, 6 who reported miR-139-5p upregulation in the serum samples of recurrence-positive CRC patients, added 25 fmol of cel-miR-39 to each sample for data normalization. Likewise, Toiyama et al 7 added 25 fmol of cel-miR-39 to each sample to normalize C t values of serum miR-200c, which is a noninvasive biomarker for CRC prognosis.…”
mentioning
confidence: 99%
“…Multiple genomics, transcriptomics and proteomics studies on discovery of prognostic markers in CRC patients had been performed. Here, we assessed the potential of metabolomics and plasma metabolic profiles in predicting metastasis in stage II CRC patients.…”
Section: Discussionmentioning
confidence: 99%